Interface regulation and electrolyte design strategies for zinc anodes in high-performance zinc metal batteries - Xun Guo; Shaoce Zhang; Hu Hong; Shixun Wang; Jiaxiong Zhu; Chunyi Zhi (iScience)
Summary: Rechargeable zinc metal batteries (ZMBs) represent a promising solution for large-scale energy storage due to their safety, cost-effectiveness, and high theoretical capacity. However, the development of zinc metal anodes is hindered by challenges such as dendrite formation, hydrogen evolution reaction (HER), and low Coulombic efficiency stemming from undesirable interfacial processes in aqueous electrolytes. This review explores various strategies to enhance zinc anode performance, focusing on artificial SEI, morphology adjustments, electrolyte regulation, and flowing electrolyte. These approaches aim to suppress dendrite growth, mitigate side reactions, and optimize the electric double layer (EDL) and Zn2+ solvation structures. By addressing these interfacial challenges, the insights presented here pave the way for designing high-performance ZMBs, offering directions for future research into scalable and sustainable battery technologies.